2015
DOI: 10.1038/nature14295
|View full text |Cite
|
Sign up to set email alerts
|

Square ice in graphene nanocapillaries

Abstract: Adsorbed layers of water are ubiquitously present at surfaces and fill in microscopic pores, playing a central role in many phenomena in such diverse fields as materials science, geology, biology, tribology, nanotechnology, etc. Despite such importance, the crystal structure of nanoconfined water remains largely unknown. Here we report high-resolution electron microscopy of mono-and few-layers of water confined between two graphene sheets, an archetypal example of hydrophobic confinement. Confined water is fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

75
765
5
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 682 publications
(858 citation statements)
references
References 48 publications
75
765
5
13
Order By: Relevance
“…In the current simulations also, after the start of Np y T equilibration at 298 K and 1 atm, the confined region between the two MoS 2 sheets becomes completely filled with water molecules in less than 200 ps if the S-to-S interlayer distance of the Interestingly, the density profiles of water for d = 6 and 8 Å are similar to those observed in graphene confined water 30 , suggesting the similar H-bond configurations of water regardless of material difference. However, the key disparity is that, for a given interlayer distance of MoS 2 sheets, clearly separated single, double, triple, and quadruple layers are seen at ambient 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 conditions; whereas for graphene, a large lateral pressure is needed not just to bring water to the graphitic confinement but also to obtain a flat configuration.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…In the current simulations also, after the start of Np y T equilibration at 298 K and 1 atm, the confined region between the two MoS 2 sheets becomes completely filled with water molecules in less than 200 ps if the S-to-S interlayer distance of the Interestingly, the density profiles of water for d = 6 and 8 Å are similar to those observed in graphene confined water 30 , suggesting the similar H-bond configurations of water regardless of material difference. However, the key disparity is that, for a given interlayer distance of MoS 2 sheets, clearly separated single, double, triple, and quadruple layers are seen at ambient 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 conditions; whereas for graphene, a large lateral pressure is needed not just to bring water to the graphitic confinement but also to obtain a flat configuration.…”
Section: Resultssupporting
confidence: 53%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29] Although the structures of confined water have been predicted for a variety of dimensions and materials using molecular dynamics (MD) simulations, the first experimental observation of the 2D water in between the two graphene sheets was obtained very recently using high-resolution transmission electron microscopy measurements (TEM). 30 This observation revealed the formation of a monolayer of planar "square" ice with a high packing density and, depending on the inter-graphene distance, the formation of bi-and trilayer crystallites of water. 30 The same authors have also reported the MD simulations of graphene-confined water that agreed with the experimental structure of the "square ice".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the interaction between Gr and CO is in the repulsion regime, and CO adsorption is destabilized in the confined space. It has been recently demonstrated that vdW forces between 2D materials can be so strong on a nanometer scale that huge pressure up to 1 GPa is built therein (40,41). Therefore, we conclude that the vdW interaction between the opposite walls of the 2D microenvironment has induced strong geometric constraint on trapped interlayer molecules, which contributes to the confinement effect.…”
Section: Resultsmentioning
confidence: 86%
“…The repulsion presented in this Letter, which is missing from classical force fields and density functional approximations, would introduce an intermolecular repulsion, which may rationalize a higher flow rate with increasing confinement. The 2D oscillator dimer example is related to a recent experiment [52] where a previously unknown ice structure has been discovered when water molecules are encapsulated between two graphene sheets, thereby suggesting peculiar intermolecular interaction between water molecules under quasi-2D confinement. In fact, a recent quantum Monte Carlo study [53] of stable square ice between graphene sheets shows that most dispersion-corrected DFT functionals overestimate the binding in the water layer.…”
Section: Prl 118 210402 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%